2009
DOI: 10.23986/afsci.5959
|View full text |Cite
|
Sign up to set email alerts
|

Productivity growth on Finnish grain farms from 1976 2006: a parametric approach

Abstract: In the long term, productivity and especially productivity growth are necessary conditions for the survival of farms and the food industry in Finland. The natural handicap and small farm size are challenges, but farmers are further challenged by the decoupling of supports and their transformation into direct income payments. Additionally, farmers' actions are limited by some institutional settings that substantially reduce incentives to improve productivity. Technical progress was found to drive the increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, it is well known that plant breeding continuously improves grain varieties. Nevertheless, as noted by Peltonen-Sainio et al (2009), this increasing yield potential is not fully utilized on Finnish grain farms. The most important reason behind this is that cereal production has become less intensive due to the application of strict environmental programmes and also reduced economic incentives.…”
Section: The Stationarity Of Exogenous Crop Yieldsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it is well known that plant breeding continuously improves grain varieties. Nevertheless, as noted by Peltonen-Sainio et al (2009), this increasing yield potential is not fully utilized on Finnish grain farms. The most important reason behind this is that cereal production has become less intensive due to the application of strict environmental programmes and also reduced economic incentives.…”
Section: The Stationarity Of Exogenous Crop Yieldsmentioning
confidence: 94%
“…The annual variation is, however, noted as a significant explanatory variable in TFP (Myyrä et al, 2009). …”
Section: The Stationarity Of Exogenous Crop Yieldsmentioning
confidence: 97%
“…The small number of observations for organic farms poses a challenge for analyzing the organic technology separately. Earlier studies (e.g., Myyrä et al 2009) have shown that technical change has been relatively slow in Finnish crop farming, whereas the variation between consecutive years has been large. Inter-annual variation is mainly explained by weather fluctuations; Schlenker (2010) has recently shown that yields are particularly sensitive to weather in cold climates such as in Finland.…”
Section: Estimationmentioning
confidence: 96%
“…The TFPG can be affected by numerous factors, including social, economic, and natural factors, and technological progress has been widely acknowledged as a key factor. For example, Myyra, S. et al (2009) highlighted the nature of grain cultivation in Finland while also considering the overall trend of the TFP and the challenges and influencing factors faced due to annual changes [27]. Li, L. et al (2010) used a DEA to determine the changes in the TFP, the sources of growth, and the determinants at the farm level, and found that land terraces and access to credit greatly contributed to the TFP and technological growth [28].…”
Section: Literature Reviewmentioning
confidence: 99%